Overview of Consumer Protection Laws Against Electronic Transactions on the Marketplace - abdul rahim (International Journal of Artificial Intelligence Research, 2022)
E-commerce has led to the emergence of web-based purchasing and selling. It has altered the conventional purchasing and selling trade, where previously direct transactions between sellers and purchasers have been replaced by indirect transactions. Shoppe is one of the Indonesian online trade exchanges that are currently expanding. Despite the fact that regulations regarding the technical implementation of e-commerce have been established, these rules still lack legal protection because parties in electronic transactions, including both sellers and buyers, are frequently harmed by parties who violate the agreement and dispute resolution offered through the platform. Consequently, the purpose of this research is to determine a market-wide overview of consumer protection laws against electronic transactions. This study employs a normative-empirical research design and a statutory methodology (law). The study's findings indicate that Indonesia's Consumer Protection Law and Information and Electronic Transactions Law have mandated consumer protection principles for e-commerce, which are acknowledged by individual customer assurances. Information, justification for web-based business exchange, standard provisions, and strategies pertaining to the purpose of online business exchange. To offer legal clarity for consumers, the Consumer Protection Act and the Information and Electronic Transactions Law allow disgruntled consumers to make claims. The government and society also play a significant role in consumer protection via their oversight duty